Profiling gene expression reveals insights into pulmonary response to aerosolized botulinum toxin type A exposure in mice. Issue 9 (2nd February 2021) - Su, Duo; Gan, Changjiao; Jiao, Zhouguang; Deng, Mengyun; Li, Sha; Ju, Yingjiao; Qiu, Yefeng; Hu, Lingfei; Gao, Bo; Zhou, Dongsheng; Zhao, Yuee; Yang, Huiying
Abstract: Botulinum neurotoxin type A (BoNT/A) is traditional medicine and well known for its therapeutic use as an anesthetic and in cosmetic applications that work through the inhibition of acetylcholine exocytosis in neuronal cells. BoNT/A also has the potential to function as a biological weapon due to its high mortality rate and ease of dispersal. Emerging evidence suggests that BoNT/A exhibits biological effects on nonneuronal cells. In cytology experiments, BoNT/A induces global gene expression alterations. However, pulmonary effects from exposure to aerosolized BoNT/A have not been evaluated. This study investigated the global transcriptional profile of lung tissues after botulism inhalation. A mice model of inhaled botulism was established using intratracheal exposure to aerosolized BoNT/A and described through histological examination and flow cytometry. Transcriptomic analysis revealed that genes related to acute inflammatory responses were upregulated at 12‐h postexposure. Increased expression of multiple anti‐inflammatory marker genes and decreased expression of pro‐inflammatory marker genes were observed at 48‐ to 72‐h postexposure, underscoring a transcriptional shift toward a pro‐reparative phenotype. Histological examination and cell proportions analysis mirrored these expression patterns. Accordingly, the orchestration of a quick phenotype transition prompted by BoNT/A may have the potential for promoting the resolution of the inflammatory lung. To our knowledge, this study represents the first research to investigate the pulmonary transcriptional responses of aerosolized BoNT/A exposure; the results may provide new insights in elucidating the molecular mechanism for pulmonary inhaled botulism and highlight the potential therapeutic application of BoNT/A in mitigating inflammatory conditions. Abstract : Lung intrinsic responses to inhaled botulinum toxin A (BoNT/A) were assessed by a temporal profile of RNA sequencing in tandem with flow cytometry and hematoxylin and eosin staining experiments. Our results highlight the ability of BoNT/A to induced acute inflammatory responses, swiftly followed by a pro‐reparative phenotype and inspire the therapeutic potentials of BoNT/A in treating inflammatory disorders.